Comics as an educational tool for children with juvenile idiopathic arthritis - Amir Mendelson; Noa Rabinowicz; Yonit Reis; Gil Amarilyo; Liora Harel; Philip J Hashkes; Yosef Uziel (BMC, 2017)
Abstract Background This study examined whether the comic book Neta and the Medikidz Explain JIA would improve disease-related knowledge and treatment adherence among patients with juvenile idiopathic arthritis (JIA). Methods In this prospective cohort study, JIA patients answered 20 multiple-choice knowledge questions about their disease, before and after reading the comic book. Demographic, clinical, health-related quality of life and adherence data were recorded and correlated to the responses. Results We studied 61 patients with a mean age of 14 ± 3.3 (range 8-18) years, 67% female, 83% Jewish and 17% non-Jewish. Thirty-nine percent had oligoarthritis, 13% systemic, 32% polyarthritis 11% psoriatic and 5% enthesitis-related type JIA. The disease was active in 46%, 40% were treated with biologics/disease modifying anti-rheumatic drugs, and 34% were in remission on medication. Among the 53 patients who completed before and after quizzes, average score increased from 63 to 80% (P < 0.001). Non-Jewish patients initially scored lower than Jewish patients (48%), but their score increased to 79% after reading the comic book. Twenty-seven patients who also completed the quiz 1 year after the first reading retained their knowledge (79%). We did not find a statistically significant correlation between knowledge and age, sex, disease subtype, or Child Health Questionnaire quality of life scores. Adherence to medication use, physical therapy and rheumatology clinic visits were high at baseline; thus, these did not change after reading the comic. Conclusions The comic booklet Neta and the Medikidz Explain JIA is a good educational tool for increasing disease-related knowledge in children with JIA.